Strategi Pemasaran Produk Dalam Meningkatkan Kepuasan Pelanggan - Rahayu, Sari (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2024)
Marketing strategy is a strategy that used by company in sustainable way to win market competition for long term. This journal aims for company to have product strategy to increase customer satisfaction. Product is a thing that could be offered to customer to be noticed, asked, looked for, purchase, used, consumed by market as a tool for fulfillment or market willingness. Product could give tangible or intangible benefit to satisfy customers potentially. Customer satisfaction is a key factor for business development. Product strategy will have an impact to customer satisfaction. Therefore, satisfied customers will buy product repeatedly and recommend that product to other customers